2009
DOI: 10.1002/mus.21236
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology in chronic inflammatory demyelinating polyneuropathy with IGIV

Abstract: Patients with chronic inflammatory demyelinating polyneuropathy (CIDP) received immune globulin intravenous, 10% caprylate/chromatography purified (IGIV-C, Gamunex; n=59) or placebo (n=58) every 3 weeks for up to 24 weeks (first period) in a randomized, double-blind, parallel-group, response-conditional, crossover study. Motor and sensory nerves were assessed at baseline and endpoint/week 24. A nonsignificant trend toward improvement in the proximal amplitude of the most severely affected motor nerve was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
(35 reference statements)
1
36
0
1
Order By: Relevance
“…Baseline values for the impairment measures—electromyographic parameters, Medical Research Council (MRC) sum score, grip strength, INCAT sensory sum score, activity and participation scale scores (INCAT disability scale and Rotterdam handicap scale (RHS)), and quality-of-life component measures (physical component score (PCS) and mental component score (MCS))—were similar between the two treatment groups 3 4 27…”
Section: Resultsmentioning
confidence: 99%
“…Baseline values for the impairment measures—electromyographic parameters, Medical Research Council (MRC) sum score, grip strength, INCAT sensory sum score, activity and participation scale scores (INCAT disability scale and Rotterdam handicap scale (RHS)), and quality-of-life component measures (physical component score (PCS) and mental component score (MCS))—were similar between the two treatment groups 3 4 27…”
Section: Resultsmentioning
confidence: 99%
“…A subanalysis of the ICE study found significantly greater improvement from baseline in favor of IVIG over placebo for averaged motor amplitudes from all motor nerves (treatment difference 0.62 mV; 95% CI: 0.05-1.20; p = 0.035) and conduction block (treatment difference -5.54%; 95% CI: -10.43 to -0.64; p = 0.027) [27]. These investigators also examined correlations between the changes observed in nerve conduction studies and response to treatment [28].…”
Section: • Markers Of Treatment Response In Cidpmentioning
confidence: 94%
“…Although precise and regular monitoring of sensory scores is seldom performed in routine clinical practice, sensory scales are commonly utilized in research settings [4,5]. The relation of clinical function with sensory electrophysiology is also uncertain, non-significant improvement of the amplitudes of sensory electrophysiological responses having been demonstrated in a recent therapeutic study [6]. We proposed to evaluate the clinical and electrophysiological sensory functions in a cohort of patients with clinically-stabilized CIDP, as well as establish the relationship with motor strength and function, and with the degree of motor axonal involvement.…”
Section: Introductionmentioning
confidence: 99%